Crowd sourcing Welsh language data in the Covid era - Evans, Jason (Septentrio Conference Series, 2021)
Welsh language place names risk being forgotten as people choose to use English versions of street names, properties, towns and villages and even rename properties with English names. Many official datasets for historic buildings in Wales do not record the original Welsh names. This presentation will look at how we have adapted our projects to work online during the Pandemic, and how we are crowdsourcing Welsh names of Wales' built heritage and adding them to Wikidata. The talk will focus on the activities of our recent Wicipics project which saw the public contribute remotely, creating Welsh language data and sharing their openly licenced images of historic sites in their area. This session will also look at how we might use this data to enrich our historic record. For example, by combining with OpenStreetMap to develop a Welsh language map interface and by sharing our crowdsourced data with 3rd party websites and other Welsh heritage organisations.